Peran Supervisi Pendidikan terhadap Peningkatan Kompetensi Guru di MAS Tarbiyatul Islamiyah - Ujang Ruslandi; Siti Qomariyah; Yuyu Yuhaeni; Vikri Dwiki (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to analyze the role of educational supervision in enhancing teacher competence at MAS Tarbiyatul Islamiyah. Educational supervision is a strategic effort to improve the quality of teaching through professional teacher development. This research employs a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. The findings reveal that educational supervision at MAS Tarbiyatul Islamiyah significantly contributes to improving teacher competence, particularly in pedagogical and professional aspects. However, the implementation of supervision faces various challenges, such as time constraints, lack of supervisor training, and teacher resistance to supervision. Administrative supervision needs to be developed into clinical supervision that focuses more on personal guidance and skill enhancement for teachers. Recommendations include strengthening supervisor training, increasing technology integration in supervision, and conducting well-planned and continuous supervision. This study provides new insights into the importance of educational supervision in supporting teacher competency development in madrasahs and offers strategic implications for improving educational quality.